(untitled) (Práxis Educativa, 2024)
This article deals with the context experienced in the educational process in the pandemic and the pedagogical practices used in school institutions with Information and Communication Technologies (ICTs). The scope of this study was to investigate the pedagogical practices used in several school institutions from 2020 to 2022. The study was characterized by being qualitative and descriptive, based on the survey of research with consultation in the Coordination for the Improvement of Higher Education Personnel Journals (Periódicos CAPES), Google Scholar and Digital Library of Theses and Dissertations (known by the acronym BDTD). The main results pointed out that there is a need for structure and teacher training, lack of public policies, obstacles in access to the internet, social losses and successful practices using active and innovative methodologies. Keywords: Pedagogical practices in school institutions. ICTs. Pandemic.